Anti-tumor promoting activity of Dicranopteris linearis (Burm.f.) underw. leaf methanol extract in a two-stage mouse skin carcinogenesis model - Rodzi, Roihanah (2017)
Dicranopteris linearislocally known as ‘resam’ has been used to treat various ailments including fever, boils, ulcers and wounds. Previous studies reported in vivo antinociceptive, anti-inflammatory, antipyretic, anti-oxidative, and anti-bacterial activity of D. linearis. Skin carcinogenesis incidence has been experiencing an increase worldwide. Constant exposure to physical, biological and also chemical assault on skin might lead to mild to severe skin carcinogenesis. Therefore, it is crucial to prevent it from happening. The present study was carried out to elucidate the chemopreventive potential of leaf methanol extract of D. linearis (MEDL) in a two-stage mouse skin carcinogenesis model since the inflammation, oxidative stress and tumor promotion pathways are interrelated. MEDL was prepared in a dose range of 30 to 300 mg/kg body weight. A total of 48 ICR female mice (6-8 weeks old) were randomly assorted into six groups. To induce skin tumor formation, a single topical application of 7,12-dimethylbenz[a]anthracene (DMBA) at 100μg/100μl was applied to the shaved dorsal region of mice, followed by repetitive administration of 1% croton oil, twice weekly for 30 weeks. Topical application of MEDL, 30 minutes prior to the croton oil application, significantly reduced the tumor incidence to 37.5% in 300 mg/kg MEDL-treated group as compared to 100.0 % in carcinogen control. The first tumor appeared at week 5 of tumor promotion period, for Group 5 (carcinogen control). Tumor in Group 1 which has been treated with MEDL at 30 mg/kg body appeared on week sixth. Tumor in Group 2 appeared on seventh week simultaneously with Group 4 (positive control) whereas the tumor formation latest appeared in week 12 for Group 3, which has been treated with MEDL at 300 mg/kg body weight. The tumor burden MEDL-treated groups (30, 100, and 300 mg/kg) were significantly lessen (25.53 ±3.23 , 5.43 ± 0.97, and 1.20 ± 0.23), as compared to carcinogen control (33.70 ± 4.25). The highest tumor volume was in carcinogen control (7.93±2.08) which is close to positive control tumor volume with the reading 7.12±1.45. Tumor volume for treated group has the reading of 18.08 ± 4.37 mm3 (highest), 0.963 ± 0.33 mm3 and 0.06 ± 0.019 mm3 in 30, 100 and 300 mg/kg MEDL-treated groups, respectively. Fresh sample of skin tissue was also subjected to antioxidant assay to determine catalase (CAT) and superoxide dismutase (SOD). As for the rest of MEDL and MEDL partition extracts, they were tested for antioxidant activity studies involving Total phenolic content (TPC), 2, 2-diphenyl-1-picrylhydrazyl (DPPH), superoxide dismutase (SOD) and oxygen radical absorbance capacity (ORAC) and anti-inflammatory study involving Lipoxygenase (LOX)-inhibiting activity and Xanthine oxidase (XO) activity. Phytochemical screening and also high-performance liquid chromatography (HPLC) were also performed to determine bioactive compound exist in the sample. The present study found that MEDL exhibited some level of inhibition of tumor promotion in dose-dependent manner with 300 mg/kg showed greatest activity, suggesting the chemopreventive potential of Dicranopteris linearis. In conclusion, MEDL exerted potential anti-tumor promoting activity, having the highest dose (300mg/kg) of MEDL performing the best. It is found that MEDL possessed high antioxidant activity but low in anti-inflammatory activity.